PENGGUNAAN MEDIA MOLYMOOD DALAM PROSES PEMBELAJARAN KIMIA UNTUK MENINGKATKAN PEMAHAMAN IKATAN KOVALEN X TKJ SMKN 13 BANDUNG - Sri Esti Widyaningsih (UJMES (Uninus Journal of Mathematics Education and Science), 2018)
The rapid development of education in the world requires the existence of a very tight competition that is supported by thedevelopment of advanced technology and information, so to be able to follow these developments require good human resources.the low interest of students in learning chemistry about covalent bonds and the lack of understanding of students in integratingthe nation character builders' value in the chemistry lesson about the covalent bonds. It is expected that learning withmolymood media can help learn mastery in comprehending covalent bond in class X TKJ SMK Negeri 13 Bandung.Chemical learning about covalent bonding requires better teacher explanation because there is much complexity inmemorizing. The method used in this research is Class Action Research. It is planned that in two cycles from the results ofthe research, the data obtained, in cycle I, the percentage of student activity is 80%, while in the second cycle to 95%. Fromthe response result, students love to learn by using molymood 90%, help understanding of subject matter 83,34%, and stillneed teacher explanation 86,67%. Constraints that are sometimes encountered include technical obstacles how to usemolymood in accordance with the child's creation and precision stringing. Completeness of chemistry study about covalentbond, there is an increase in post test value of cycle II by 27% from cycle I which is above KKM.